A survey of burnout and professional satisfaction among United States neurointerventionalists. (11th April 2019) - Fargen, Kyle M; Arthur, Adam S; Leslie-Mazwi, Thabele; Garner, Rebecca M; Aschenbrenner, Carol A; Wolfe, Stacey Q; Ansari, Sameer A; Dabus, Guilherme; Spiotta, Alejandro; Mokin, Maxim; Linfante, Italo; Mocco, J; et al.
Abstract : Background: The toll of burnout on healthcare is significant and associated with physician depression and medical errors. Objective: To assess the prevalence and risk factors for burnout among neurointerventionalists. Methods: A 39-question online survey containing questions about neurointerventional practice and the Maslach Burnout Inventory-Human Services Survey for medical personnel was distributed to members of major US neurointerventional physician societies. Results: 320 responses were received. Median (interquartile range) composite scores for emotional exhaustion were 25 (16–35), depersonalization 7 (4–12), and personal accomplishment 39 (35–44). 164/293 respondents (56%) met established criteria for burnout. There was no significant relationship between training background, practice setting, call frequency, or presence of a senior partner on burnout prevalence. Multiple logistic regression analysis showed that feeling underappreciated by hospital leadership (OR=3.71; p<0.001) and covering more than one hospital on call (OR=1.96; p=0.01) were strongly associated with burnout. Receiving additional compensation for a call was independently protective against burnout (OR= 0.70; p=0.005). Conclusions: This survey of United States neurointerventional physicians demonstrated a self-reported burnout prevalence of 56%, which is similar to the national average among physicians across other specialties. Additional compensation for a call was a significant protective factor against burnout. In addition, feeling underappreciated by departmental or hospital leadership and covering more than one hospital while on call were associated with greater odds of burnout.